The Reliability of Positive and Negative Work Reflection Scales: Reliability Generalization Meta-Analysis - Vadvilavičius, Tadas (Psichologija, 2025)
Positive and Negative work reflection are important constructs in the field of organizational psychology. To measure these constructs, reliable measures are needed. In order to summarize the findings from different studies, a reliability generalization meta-analysis was performed. A literature search in six databases was conducted. In total, 216 records were found, while 26 papers were included in the analysis. Positive and Negative work reflection scales by Fritz and Sonnentag (2005) and Binnewies et al. (2009) were analyzed. Analysis revealed that internal consistency varied from 0.90 to 0.93. Additionally, the region in which a study was conducted moderated part of the results.
Keywords: meta-analysis; positive work reflection; negative work reflection; reliability